Professional Skills Development Through the Network Learning Community Using an Online Learning Platform - Ashar, Muhammad; Kamdi, Waras; Kurniawan, Dediek Tri (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Networked learning Community (NLC) that integrates a professional context into the learning experience that uses learning networks to promote self-efficacy and professional development. Online Learning design integrates three techniques: focus on developing personal learning networks, live streaming and online based learning communities and immersive skills and experience mastery for professionals. The hypothesis is that networked learning community among peers in the online learning will help support skills development and confidence in sustainable use of the platform in a personalized way. Meanwhile networking for learning with professionals will strengthen the impact of mastery experience on self-efficacy. Learning experiences as relevant for lifelong learning and professional success are important in today’s learning era. NLC aligned with the goals of the 21st century skills movement can be an important mechanism for scaling up efforts to redesign academies that offer skills with a forum for broad but personal learning. The live streaming technique in the learning process in online media has a significant impact in monitoring and monitoring one-on-one learners’ abilities. Learning outcomes can be easily corrected and evaluated by relevant experts so that the work can be used as a good portfolio. In the application of the NLC the target output is that there is a promotion mechanism for students to the industrial world by bringing together professional companies and / or developing entrepreneurship with the addition of business training to the relevant NLC. The results of the platform development show that the flow and process of improving skills and professional learning with the community in one field of multimedia industry is getting better